THE ROLE OF SOCIAL NETWORKS AND MOBILE APPLICATIONS IN PHYSICAL ACTIVITY DURING THE COVID-19 EPIDEMIC IN SERBIA: THE ROLE OF SOCIAL NETWORKS AND MOBILE APPLICATIONS IN PHYSICAL ACTIVITY - Milic, Natasa; Savic, Nikola; Rajović, Nina; Milin-Lazovic, Jelena; Marko, Marko; Milic, Nikola; Milcanovic, Petar; Markovic , Ksenija; Stanisavljevic, Tamara; Nesic, Dejan; Mazic, Sanja (Medical Research, 2022)
After the outbreak of the novel SARS-COV-2 coronavirus, in the Chinese province of Wuhan that spread rapidly across the world, the Government of the Republic of Serbia introduced protection measures in March 2020, to prevent the spread of the infectious disease COVID-19 in Serbia. All gatherings indoors (sport, cultural and other events), as well as in parks and public places intended for recreation and sports, were prohibited. Shortly after, a lockdown took place which prohibited leaving home with the exception of basic needs, work from home was recommended and online schooling was introduced. The World Health Organization has recommended the use of online resources to maintain basic physical activity. In these circumstances of social distancing, this study examines the prevalence of physical activity supported by social networks and mobile applications during the COVID-19 lockdown in Serbia. The study was conducted as a cross-sectional study, using questionnaire distributed through social networks. The study found that more than a third of respondents (38.3%) used social networks or mobile apps to perform physical activity during the lockdown in Serbia; 27.1% used social networks/mobile apps before the pandemic, while 11.2% began to use social networks/mobile apps to perform physical activity during the lockdown. Easy access and review of exercises were the most common reasons for using social networks/mobile apps. 40% of the participants in the study agreed that social networks/mobile apps, make it easier to engage in physical activity. Based on the presented results, it can be concluded that the promotion of physical activity at home through social networks and mobile apps can provide an invaluable contribution to maintaining physical activity globally during pandemics such as COVID-19.Key words: physical activity, mobile applications, social networks, COVID-19,pandemics, lockdown
Keywords: physical activity; mobile applications; social networks; COVID-19; pandemics; lockdown